ANALISIS PENGELOLAAN MODAL KERJA DALAM RANGKA PENILAIAN PRODUKTIVITAS PERUSAHAAN (Studi pada Pabrik Roti Pelangi Nusantara Kota Metro) - Irsa Yolanda; Jawoto Nusantoro; Yulita Zanaria (Jurnal Akuntansi AKTIVA, 2021)
The purpose of this study was to analyze working capital management related to company productivity at the Pelangi Nusantara Bakery Factory in Metro City. The method used in this study is a quantitative method with the object of research being the management of working capital and company productivity. The data collection technique uses documentation on reports for 4 years, 2015-2018. The analytical tool used is an analysis of the company's financial statements in the form of analysis of cash turnover, inventory, accounts receivable, working capital, GPM, NPM and productivity ratios. The results of the analysis show that cash turnover and accounts receivable turnover each year are included in the good cash turnover category, while inventory turnover is in the poor category. Gross Profit Margin in good category, Net Profit Margin in good category although not experiencing a significant increase. The productivity ratio tends to remain or not increase due to an increase in the price of raw materials and a decrease in the value of the currency which causes the value of the assets involved to increase.